Avaliação do aplicativo de tecnologia móvel Android C7 Leite: zootecnia de precisão - Agnol, Sidnei Dal (2016)
Nowadays those who live or work in the countryside have increasingly access to technologies that favor the development of their daily activities. Smartphones and tablets with android operating systems, which are every day more accessible to the farmers, offer opportunities for the use of applications that support them in decisionmaking. These new tools are available to the rural man, rural extension and/or technical assistance professionals, and can be used to increase the competitiveness of their properties. This study aimed to assess the C7 Milk II application to find out its strengths and weaknesses, as well as to contribute to the provision of a free management system, which is efficient and easy for the farmers and technicians to use, positively influencing the management of dairy farming properties. Thus we tested the use of this application in two family farms: one in the city of Alto Alegre/RS and another in the city of Espumoso/RS. We accompanied the development of the activities related to the tool use, and recorded the farmers´ perceptions on it. We also used contacts and questionnaires to find out the perception of field technicians who work in the region in order to identify the potential and limitations of the use of the applications among the rural men. At the end of the study, we found out that the application has potential as a tool to give greater precision to the dairy management, since it has several strengths. However, it also has some weaknesses, which need to be improved to have greater acceptance by farmers and technicians. Among the limitations of the application use, there are some difficulties for the farmers to adopt a notes routine about the activity, as well as their lack of ability to work with new technologies. These aspects impair their use in a big scale as a complementary tool in the management of dairy farming. The agility and the mobility of the tool; the generating of information for decision-making with low cost access and application service; and the farmer´s thinking on his activity have being considered potential factors.